PARADOKS EFEKTIVITAS MBS: KONTRADIKSI ANTARA KEUNGGULAN TATA KELOLA INTERNAL DAN KETERBATASAN DUKUNGAN FINANSIAL SEKTORAL - Chindytia; Anak Agung Gede Agung; Ni Komang Dyah Tri Rahma Wraspati; Ni Kadek Dina Yuliartini; Anak Agung Istri Mirah Pradnya Paramitha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the paradoxical phenomenon between the quality of internal school governance and the reality of infrastructure limitations at SD No 3 Sading. A descriptive qualitative approach using the case study method was employed, with data collected through observation, interviews, and School-Based Management (SBM) assessment instruments. The results show that, quantitatively, SBM implementation is in the